The Role of The Press Council in Enforcement of The Press Law - Indrianti Azhar Firdausi (Future Science, 2021)
This study aims to examine the role of the press council in enforcing the press law and journalistic code of ethics where digital developments are currently very developed, especially media that utilize new media platforms. Not all online mass media are legal entities and not all news that is conveyed through online media follows a journalistic code of ethics, giving rise to overlapping perceptions and activities due to the lack of understanding of journalists and the public in the midst of easy access to information. This research uses a descriptive qualitative approach with a case study method, data collection is collected through observation and documentation sourced from literature and document studies that examine the phenomenon of digitalization dynamics around press laws and journalistic codes of ethics. There are a number of efforts from the press council, including enforcing the press law on online mass media by carrying out a number of verification processes including administrative verification, factual verification and content verification. The third verification cannot be carried out because of the constraints of human resources and budget. A mass media that receives a report will be handled and mediated by the press council if the mass media is already a legal entity. Meanwhile, the enforcement of the press code of ethics is carried out by first classifying journalism activities based on whether the mass media is a legal entity or not, then screening complaints of violations of the code of ethics, and reprimanding the problematic mass media to apologize and clarify the misinformation that has been published.